PELAKSANAAN PROGRAM KELUARGA BERENCANA DI KECAMATAN MELAK KABUPATEN KUTAI BARAT - Lukman Hakim (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
This study aimed to examine the implementation of family planning programs in the district of Melak, West Kutai Regency especially in terms of communication, resources, disposition, bureaucratic structure and identify the factors supporting and hindering the implementation of the family planning program in the district of Melak, West Kutai Regency. In this research, writer use the qualitative approach. Data collecting conducted by doing cirscumtantial interview, sharing observation and also documentation study. After this phase, is done by a data analysis qualitative that use the interactive model analysis. The results showed that the implementation of the family planning program in the District Melak not run well. This is caused by the lack of family planning and their extension number of cadres, the facilities were incomplete and lack of budget from the government for the implementation of family planning programs. Keywords: public policy, implementation, family planning